Досвід розробки твердотільних малошумних підсилювачів НВЧ для радіолокаційних станцій - Харченко, С. О. (ХНУРЕ, 2024)
Experience of developing solid-state low-noise UHF amplifiers designed to replace traveling-wave tube in radar receiving channels is presented. Analysis of various types of protective devices at amplifiers inputs is carried out, parameters of production-run equipment is provided.
Keywords: малошумний підсилювач; підсилювач НВЧ для радіолокаційних станцій